Analisis Nilai Etika Tolong Menolong dalam Novel Harga Sebuah Percaya Karya Tere Liye - Erlina Zahar; Sujoko Sujoko (Universitas Batanghari Jambi, 2021)
This study aims to analyze the ethical value of helping in the novel Harga Sebuah Percaya by Tere Liye. This type of research is literary research, which is descriptive qualitative. The research data are taken from the novel Harga Sebuah Percaya by Tere Liye, namely words, sentences, and paragraphs related to the ethical value of helping to help. The data source of this research is the novel Harga Sebuah Percaya by Tere Liye. The data collection technique in this research is to use documentation and literature studies to analyze the contents of a novel, especially the ethical value of helping to help in the novel Harga Sebuah Percaya by Tere Liye. The results of the study show that the ethical value of helping to help contained in the Harga Sebuah Percaya by Tere Liye is 27 quotes.